Structural Incorporation of As5+ into Phosphosiderite by a Strengite/Scorodite–like Arrangement. Issue 14 (6th September 2016) - Bolanz, Ralph M.; Wierzbicka‐Wieczorek, Maria; Giester, Gerald; Göttlicher, Jörg; Steininger, Ralph
Abstract: Phosphosiderite (FePO4 ⋅2H2 O) is the monoclinic ( P 21 / n ) polymorph of orthorhombic strengite (Pbca), which is isostructural to scorodite (FeAsO4 ⋅2H2 O). While the structural incorporation of As 5+ into strengite can be attributed to a fractional miscibility between strengite and scorodite, the incorporation of As 5+ into phosphosiderite and its dehydration product FePO4 ( P 21 / n ) has never been investigated until now. Phosphosiderite, synthesized under hydrothermal conditions at 200 °C in the presence of arsenic, incorporates 0.044±0.001, 0.084±0.001, 0.165±0.002, 0.425±0.004 and 0.844±0.014 wt.% As at initial molar As/Fe solution ratios of 0.05, 0.1, 0.2, 0.5 and 1, respectively. With increasing As content, the P concentration in phosphosiderite decreases by 1.02 to 1.58 P atoms for each incorporated As. The unit‐cell parameters a, b, c and β increase from As‐free phosphosiderite with 5.326(6) Å, 9.793(8) Å, 8.709(3) Å and 90.54(0)° to 5.329(0) Å, 9.797(5) Å, 8.713(7) Å and 90.56(7)°, respectively, for phosphosiderite synthesized at an initial molar As/Fe solution ratio of 1. Single crystal X‐ray diffraction indicates that the P position in phosphosiderite is occupied by As with about 2 %. X‐ray absorption spectroscopy displays only As 5+, which resides on the P position in phosphosiderite in a local coordination similar to strengite and scorodite, indicating the structural incorporation of As 5+ into a strengite/scorodite‐like arrangement. Abstract : Combined long and short‐range order investigation on the homovalent substitution of P 5+ by As 5+ in phosphosiderite . Phosphosiderite (FePO4 ⋅2H2 O) is the monoclinic polymorph of orthorhombic strengite and incorporates up to 2 wt.% of As by homovalent substitution. X‐ray absorption spectroscopy indicates, that the local coordination of As 5+ in phosphosiderite is unlike P 5+ and corresponds to a structural arrangement similar to strengite or scorodite (FeAsO4 ⋅2H2 O).